(untitled) (Research Journal, 2023)
A range of terminologies is used by LGBTIQ+ individuals to express themselves and their community. Equality and discrimination-free treatment are essential human rights that apply to all people, regardless of sexual orientation or gender identity. In most societies, LGBTIQ+ people are persecuted, marginalized, or at risk. The LGBTIQ+ movement is simply a social movement advocating gender equality and acceptance of all genders. In Nepal, this movement is extremely necessary as sexual minorities are sometimes not treated as humans and they face discrimination, oppression, violence, abuse, and biasness. This article is written to introduce sexual minorities as an important section of society and highlight the importance of LGBTIQ+ acceptance for a better society. The objective of this study is to explore the existing laws and create a sense of better awareness among the readers. Explorative, qualitative, and descriptive designs and secondary data have been used to satisfy the objectives of this research. This article composes of a short description of the role of laws, state policies, and mechanisms of the legal courtroom in assuring LGBTIQ+ rights in Nepal. The resume of this research is to conclude that every society should cherish and respect every gender, and the legislation should act likewise.